Fraud Detection in the Banking System in Nigeria: Challenges and Prospects - Badejo, B.A; Okuneye, B.A; Taiwo, M.R (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
Fraud is an epidemic dimension that has eaten deep into the banking sector as well as the entire economics in Nigeria. Its devastating effect manifests itself in the deteriorating balance sheet of banks as well as in economic backwardness. Apparently, measures to detect and eradicate fraud in banking sector have been quite ineffective as the fraudulent practices have been on the increase in recent times. Thus, this study evaluates the various challenges of detecting and combating fraud in the banking sector in Nigeria. The results from the descriptive analysis showed that lack of adequate motivation is not a major cause of fraud in banks, looting of fund by bank managers and directors constitutes the major form of fraud in Nigeria. Furthermore, it is recommended that government should strengthened existing anti-graft agencies and to enhance their financial independence. Those managers and director involved in looting of fund should be persecuted to serve as a deterrent to potential fraudsters. In addition, bank staff should be properly screened to test their morality and integrity before recruitment. Adequate internal control mechanism should be established to serve as check and balances among the bank staff. There is also the need for the anti-graft agencies to be strengthened in order to adequately complement the effort of the Central Bank of Nigeria (CBN) at nibbling the incidence of bank fraud in the bud.Keywords: banking system, fraud, fraud detection, fraud prevention, Nigeria